1981
DOI: 10.1139/v81-028
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of a soil fulvic acid with precipitating hydrous ferric oxide at pH = 6

Abstract: A kinetic method of analysis which distinguishes Fe(II) from Fe(III) and Fe(III) forms of various labilities from each other is based on spectrophotometric monitoring of the reaction of Fe(II) with ferrozine. Reduction of Fe(III) with hydroxylamine hydrochloride allows the single colourimetric reagent to detect all forms of Fe. The method is applied to study of the effects of a well characterized soluble soil organic acid sample, a fulvic acid, on the speciation of Fe(III) under conditions (pH = 6) where Fe(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Studies of the kinetics of ligand-exchange reactions of transition metals (reviewed in ref 4) have shown the reactions to proceed by direct attack of the incoming ligand on the initial metal complex usually with rate-determining dissociation of the intermediate ternary complex thus: In contrast, Shuman and co-workers have observed that ligand-exchange reactions of Cu-DOC complexes involve dissociation of the initial copper complexes and have reported rate constants for the dissociation of these complexes (5)(6)(7). Other studies of reactions of húmateor fulvate-metal complexes or of reactions of metals with humic or fulvic acids have focused on different metals-Fe (8)(9)(10)(11), Al (12,13), Ni (14), and Th (15,16).…”
Section: Background and Theorymentioning
confidence: 99%
“…Studies of the kinetics of ligand-exchange reactions of transition metals (reviewed in ref 4) have shown the reactions to proceed by direct attack of the incoming ligand on the initial metal complex usually with rate-determining dissociation of the intermediate ternary complex thus: In contrast, Shuman and co-workers have observed that ligand-exchange reactions of Cu-DOC complexes involve dissociation of the initial copper complexes and have reported rate constants for the dissociation of these complexes (5)(6)(7). Other studies of reactions of húmateor fulvate-metal complexes or of reactions of metals with humic or fulvic acids have focused on different metals-Fe (8)(9)(10)(11), Al (12,13), Ni (14), and Th (15,16).…”
Section: Background and Theorymentioning
confidence: 99%
“…The kinetic method of analysis employed has been used successfully to study distinguishable components of colloidal mixtures of Fe(II1) hydrous oxides and the corresponding fulvic acidiron colloids (7,8 components it is reasonable to try to resolve from the data and one needs physically reasonable initial values of total concentrations and rate constants to put into the iterative process. One could assume a continuurn of rate constants for the mixture called fulvic acid and examine the form of the distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This fulvic acid was chosen since it has been well-characterized by Gamble and Schnitzer (9,10). The number average molecular weight of 900 used earlier (11) was used to calculate "molar" concentrations. To appreciate the complexity of the sample, it is worth noting that the weight average molecular weight is near 5000.…”
mentioning
confidence: 99%